Writing the French sculptor: the operations of exclusivity in the critical discourse of Émile-Antoine Bourdelle, 1918–31. Issue 2 (2nd April 2020) - Rose-Curti, Gabrielle
Abstract: This article examines the prolific French critical promotion of the sculptor Émile-Antoine Bourdelle published between 1918 and 1931, and argues for its direct function in the cultural politics of rappel à l'ordre conservatism in France. Authored by numerous art critics and writers, these texts collectively sought to secure Bourdelle as the supremely French sculptor of the contemporary era. In so doing, they provide a richly layered and largely unexplored ideological discourse that served, and indeed helped write, the period's rhetoric of French national recovery and, ultimately, exclusivity. The persuasive language of these texts maneuvered around certain problematic realities of Bourdelle's style, process, affiliation, even adverse critical assessment, to herald the man and his sculpture as vitally reconstituting France's authentic, and heretofore lost, self—its classical and medieval art forms and allied principles of discipline and collective appeal. This claim was made, moreover, through a complex of naturalizing, racialist, and gendered constructs that equipped Bourdelle—as sculptor and as national body—in inviolable terms against "un-French" artistic "infiltrations, " past and present.